The envisaged reformation of interim measures of protection under the UNCITRAL Model Law - can the new German Code of Civil Procedure serve as a role model? - Scheiffele, Kai-Olaf (Department of Commercial Law, 2023)
When the United Nations Commission on International Trade Law (UNCITRAL) assembled in Vienna between May 17 and June 4, 1999, it decided that the time had come for an evaluation on how to further develop arbitration laws, rules and practices. Some fourteen years earlier, on December 11, 1985, UNCITRAL created the Model Law on International Commercial Arbitration (MAL) to achieve uniform standards of arbitral procedure. These were regarded as necessary since international arbitration became increasingly important in order to solve the growing numbers of disputes arising in international business transactions. The expected purpose of the Model Law was to reduce the differences in national procedural laws so that international arbitrators would only have to battle with the multitude of national substantives law to decide upon the merits of the case. Without hesitation, it may be claimed that it did fulfil this task, as it became a "vehicle to achieve the widest possible acceptance and (. .. ) greatest degree of harmonisation of national law. Already 50 countries, including not only prominent trading nations like Germany, Canada, India and Russia, but also numerous emerging nations have introduced the Model Law with only minor modifications if any at all. It has in the meantime inspired most other countries that were drafting a new procedural law concerning arbitration. For example the United Kingdom paid close regard to the Model Law when passing the Arbitration Act 1996. The reason for the successful launch of this Model Law is that it concentrates on merely providing the basis for a legal system and shows a great degree of flexibility. At the same time, it is very sophisticated and includes a reliable set of rules required to conduct a predictable arbitral proceeding. For this reason, the provisions of the modernised Code of Civil Procedure ("Zivilprozessordnung", ZPO) in Germany, where arbitration is used widely in practice, are to great extent translations of the Model Law. They will be discussed extensively in this thesis. However, in the course of its 32nd session, UNCITRAL realised the need for arbitration to adapt to the new economic world order that had experienced a radical change since the Model Law came into existence. At the same time, UNCITRAL recognised the major importance for this institute of dispute resolution to be equipped with competitive procedural rules to carry on its growth as an "arbitration service industry". Therefore, the Working Group on Arbitration and Conciliation was established. It was meant to determine the areas where arbitral tribunals may fail to meet the demands of its potential clients. The Working Group found that the availability of interim measures of protections is regarded as one of arbitration's major weakness and thus shall be made the priority item. These measures, also referred to as "provisional orders", "conservatory measures" or "protective measures", may provide that arbitrational agreements as well as the awards they result in are enforceable. Especially in international disputes, they may be required to preserve essential rights of the parties situated in different jurisdictions. Yet it is often felt that the Model Law would fail to provide the arbitral tribunals with a solid competence to order effective interim measures; it would lack a clear definition to make their application more reliable and predictable. Finally, a large amount of uncertainty exists about the way that interim measures can be enforced. Therefore, a wide consensus exists that the Model Law needs to be reformed in this area. The last time the Working Group of UNCITRAL met to discuss this ambitious project was in New York between February 23 and 27, 2004. During this 40th session of the Working Group various amendments to the Model Law were considered however no final conclusion could be found. Unfortunately these efforts at reform seem to have gotten stuck and, up to date, have only resulted in a declaration of intentions. In this thesis I will describe the challenges faced by arbitral tribunals that are indirectly applying the Model Law when interim measures of protection become necessary. I will focus on possible solutions to overcome these problems. Specifically I will consider the potential use of the experience in Germany by evaluating the relevant provisions of its Code of Civil Procedure and commenting on how these could benefit a revision of the Model Law.